Efisiensi Perancangan Meterisasi Lampu Penerangan Jalan Umum Kecamatan Tuntang Kabupaten Semarang - Nugroho, Agung (Transmisi, 2008)
Street Lighting Lamp (SLL) is the city or regency government public service for security and  regularity of the  street area environment.As the number of  SLLs increased there are illegal installation of SLL making the unpredictable billing for the government and increasing the budget. To solve the problem, the power consumption measurement must be implemented  to get the efficient billing. There are such devices can be used as measurement or meterization like KWH-meter or MeasurementLimiter Device.Keywords: Street Lighting Lamp (SLL), power consumption, KWH-meter, MeasurementLimiter Device